PERAN PENDIDIKAN KARAKTER DALAM MENINGKATKAN KESADARAN ETIKA DAN MORAL SISWA KELAS IX SMP SWASTA MARISI MEDAN - Mawar Hutabarat , Nova; Maranata Simangunsong, Reni; Pilia Br Surbakti, Reka (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of character education in increasing the ethical and moral awareness of ninth-grade students at Marisi Private Junior High School, Medan. Using a qualitative descriptive case study method, data were collected through observation and interviews. The results indicate that character education plays a significant role and is actively implemented through three main pillars: teacher role models, the integration of values ​​across all subjects, and structured habituation programs (such as Morning Assembly). This implementation has successfully increased students' ethical and moral awareness, as evidenced by increased participation in cleanliness, adherence to rules, and more polite interactions. Character education has proven to be an effective instrument in shaping students' behavior with integrity and responsibility.